Hubungan Konsumsi Lemak Dan Aktivitas Fisik Dengan Kadar Kolesterol Darah Dan Kadar Low Density Lipoprotein Pada Pasien Penyakit Jantung Koroner Rawat JalanDi Rumah Sakit Umum Daerah Dr. Moewardi - KURNIAWATI, Fauziah Khusnul, Ririn Yuliati S.Si.T., M.Si, Elida Soviana, S.Gz., M.Gizi (2015)
Background: Coronary Heart Disease (CHD) is one of the leading cause of death in the world. One factor that is the cause of CHD is dyslipidemia. Dyslipidemia is a disorder of lipid metabolism that is the state of the increase in blood cholesterol levels, LDL, trglyserides and decreased HDL. Increased of blood cholesterol levels and LDL levels can be caused by high consumtion patterns of that fat and physical inactivity. Objective: To determine the relationship between fat consumption and physical activity with blood cholesterol and LDL levels in patiens of coronary heart disease in outpatient Hospital Dr. Moewardi. Research Method: The research was an observational with cross-sectional approach. The technique of sampling with consecutive sampling approach with total sample research as much as 33 patients. The fat consumption obtained by the method of semi FFQ. Data of physical activity were obtained using recall activity wheres blood cholesterol levels and LDL is obtained from laboratory test data. The statistical test used Rank Spearman. Result: The number of subjects with fat consumption is not good category of 60.6%. Subjects with mild physical activity amounted to 57.6%. Blood cholesterol levels are the subjects of most of the normal categories of 78.8%. LDL levels are the subject of most of the normal categories of 72.7%. There is relationship between the fat consumption in blood cholesterol levels (p=0,016). There is relationship between the fat consumption in LDL levels (p=0,036). There is relationship between the physical activity in blood cholesterol levels (p=0,013). There is relationship between the physical activity in LDL levels (p=0,021). Conclusion: There is significant relationship between fat consumption with blood cholesterol levels and LDL levels. There is significant relationship between physical activity levels of blood cholesterol and LDL levels.